On the Inheritance of Red Flag Canal Spirit in University Campus - Ling Ling Lu; Wanying Cui (IJRDO- Journal of Educational Research, 2019)
Based on the analysis of the background and connotation of the spirit of the Red Flag Canal, this paper analyzes the essence of Red Flag Canal Spirit. Next, we accurately grasp the current status of Red Flag Canal Spirit in the university campus and the ideological education and lifestyle of college students. Based on the current situation, combined with the current reality, we put forward a path to strengthen the spirit of the Red Flag Canal in the majority of teachers and students.